2018
DOI: 10.1007/s11262-018-1554-3
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of A-549 cells infected with human adenovirus 40 by LC-MS

Abstract: Human Adenoviruses (HAdVs) are etiological agents of different syndromes such as gastroenteritis, cystitis, ocular, and respiratory diseases, and infection by these viruses may cause alterations in cellular homeostasis. The objective of the study was the proteomic analysis of A-549 cells infected with HAdV-40 using LC-MS. At 30 h of infection, the quantitative analysis revealed 336 differentially expressed proteins. From them, 206 were induced (up-regulated) and 130 were suppressed (down-regulated). The majori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…In the present study, the induction of apoptosis was not observed at 24 hpi, whereas proteins related to the apoptotic process like Annexin were found to be induced at 48 hpi. These data were observed also in other studies conducted with HAdV‐2 and with other HAdVs …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the present study, the induction of apoptosis was not observed at 24 hpi, whereas proteins related to the apoptotic process like Annexin were found to be induced at 48 hpi. These data were observed also in other studies conducted with HAdV‐2 and with other HAdVs …”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, it has been admitted that the virus needs to control host cell machinery to complete its replication while avoiding cellular defense mechanisms. Different studies have been performed focusing on adenovirus structure whereas few others were conducted aiming to study the interaction of some HAdVs types such as 5, 12, and 40 with host cell in the context of identification of the differentially expressed proteins …”
Section: Discussionmentioning
confidence: 99%
“…An LC-MS proteomic study of A549 cells infected at confluency with HAdV species F type 40 (HAdVF-40) (Table 1) and examined at 30 hpi indicated that 206 host-cell proteins were upregulated and 130 host-cell proteins were downregulated by infection [48]. Many of these were involved in metabolism and energy production pathways.…”
Section: Metabolomic and Proteomic Analyses Of Adenovirus Infectionmentioning
confidence: 99%
“…Many of these were involved in metabolism and energy production pathways. Specifically, these included glycolysis, the TCA cycle, cellular respiration, beta-oxidation, the PPP, and amino acid metabolism [48]. Interestingly, the authors observed higher mitochondrial activity in HAdVF-40 infected cells [48].…”
Section: Metabolomic and Proteomic Analyses Of Adenovirus Infectionmentioning
confidence: 99%
See 1 more Smart Citation